Marriage Kinship in the Customary Marriage Institution in Seith Negeri, Ambon Island - Alfons, Christwyn Ruusniel; Soselisa, Hermien L.; Titaley, Elsina (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
Traditions in indigenous communities on Ambon Island are found in various aspects of life. Relatively, traditions become rules or guidelines for the community to carry out their life activities in the economic, political, legal, socio-cultural, and other fields. Of course, the ancestors placed this effort to avoid irregular living behavior so that the community would feel peace and comfort. Therefore, the basis laid for generations will become a reference for acting and building a life together, such as marriage kinship in the traditional marriage process in Negeri Seith, Ambon Island. Seith, as a Muslim negeri, provides space for the mechanism of customary practices of its community, especially in the tradition of marriage. Therefore, marriage kinship receives recognition and is integrated into marriage religiously. This reality illustrates that traditional and religious institutions do not compete but together contribute to strengthening society and its people who want to build a new household. This research aims to reveal, discover, and analyze the value and meaning of marriage kinship in the traditional marriage process in Negeri Seith. The research method used is qualitative, using interview and observation data collection techniques. Indeed, this is important to show the objective reality of the community carrying out customary rules regulated by ancestors and the provisions of God Almighty through religious institutions. The marriage kinship is the marriage guardian, and the bride-to-be's father's relatives determine that religious marriage will be carried out if it is by these provisions.